1096 Robot-Assisted Minimally Invasive Oesophagectomy: Comparing the Geography of Research Publication with The Global Burden of Disease. (12th October 2021) - Higginbotham, G; Zucker, B; Ramirez, J; Kirkham, E N; Jones, C S; ,
Abstract: Introduction: Robot-assisted minimally invasive oesophagectomy (RAMIE) is increasingly used in the management of oesophageal tumours. It is unclear if there is equitable access to this innovative technique worldwide, specifically in areas of greatest need. This study aimed to map the geographic distribution of publications on RAMIE and compare this to global disease burden. Method: Systematic searches identified all studies of RAMIE from inception to 2020. The country of origin of each study was identified. The incidence and age standardised rate (ASR) of oesophageal cancer for each country was obtained from The Global Cancer Observatory (GLOBOCAN) database. World Bank classifications of countries by income level were obtained. Results: A total of 103 studies were identified. The majority (81%) were published in high-income countries, 15% in upper-middle, and 5% in lower-middle income countries. Thirty-four were published in the USA, the country with the fifth-highest incidence of oesophageal cancer worldwide, but 90th by ASR. The greatest incidence was in China (54% of global incidence) but was the source of only 15% of studies. Of the ten countries with the highest incidence, five were represented in published studies, in comparison to one of the top 10 by ASR. Conclusions: There is evident disparity in the geographical distribution of published studies of RAMIE. This disparity may represent unequal access to surgical technologies, or a lack of evaluation of the technology in different healthcare settings. This may impact the generalisability of research findings. Equitable access to novel surgical technologies is ethical and can help address global disease burden.